Effect of surgical stabilization of rib fractures in polytrauma: an analysis of the TraumaRegister DGU(R) - Becker, Lars; Schulz-Drost, Stefan; Spering, Christopher; Franke, Axel; Dudda, Marcel; Lefering, Rolf; Matthes, Gerrit; Bieler, Dan (European Journal of Trauma and Emergency Surgery, 2022)
Purpose In severely injured patients with multiple rib fractures the beneficial effect of surgical stabilization is still unknown. The existing literature shows divergent results and especially the indication and the right timing of an operation are subject of a broad discussion. The aim of this study was to determine the influence of a surgical stabilization of rib fractures (SSRF) on the outcome in a multi-center database with special regard to the duration of ventilation, intensive care and overall hospital stay. Methods Data from the TraumaRegister DGU(R) collected between 2008 and 2017 were used to evaluate patients over 16 years with severe rib fractures (AIS >= 3). In addition to the basic comparison a matched pair analysis of 395 pairs was carried out in order to find differences and to increase comparability. Results In total 483 patients received an operative treatment and 29,447 were treated conservatively. SSRF was associated with a significantly lower mortality rate (7.6% vs. 3.3%, p = 0.008) but a longer ventilation time and longer stay as well as in the intensive care unit (ICU) as the overall hospital stay. Both matched pair groups showed a good or very good neurological outcome according to the Glasgow Outcome Scale (GOS) in 4 of 5 cases. Contrary to the existing recommendations most of the patients were not operated within 48 h. Conclusions In our data set, obviously most of the patients were not treated according to the recent literature and showed a delay in the time for operative care of well over 48 h. This may lead to an increased rate of complications and a longer stay at the ICU and the hospital in general. Despite of these findings patients with operative treatment show a significant lower mortality rate.
CRIS-Team WoS Importer:2022-02-18